أثر استخدام الأساليب الكمية في واتخاذ القرارات بالتطبيق على مصنع سكر كتانة - د السماني محمد الغالي نور الدائم عبد المحمود (White Nile Journal for Studies and Research, 2026)
the effect of using the quantities method in analyzing the problems and making the decisions applying Kenana sugar factory aims mainly to identify and measure the effects of using the quantities methods in analyzing and making the decisions and not paying attention to the making decisions process in the administrative problems which reflects negatively on the work force.. continuity the competition. the works results and the performance generally. and the important results that came out from this research the degree of knowledge about the quantities methods represents a huge percent in the position of making the decisions the university studies and the post graduate studies represents of the qualifications of those who makes the decisions and it is a huge percent the majority of the users to this method using a specific amount methods due the lack of knowledge about the other quantity methods The university studies represents the first source of the knowledge of this method cause the universities were the first to teach this method and the scientific research methods to the students from over 30 years ago There is a huge desire from those who knows or doesn't know the quantity